Regulation Mechanisms of the Hedgehog Pathway in Pancreatic Cancer: A Review - Honselmann, Kim Christin; Pross, Moritz; Jung, Carlo Maria Felix; Wellner, Ulrich Friedrich; Deichmann, Steffen; Keck, Tobias; Bausch, Dirk (JOP. Journal of the Pancreas, 2015)
Pancreatic ductal adenocarcinoma (PDAC) is the fourth most common cause of death from cancer. Its 5-year survival rate is less than 5%. This poor prognosis is mostly due to the cancer’s early invasion and metastasis formation, leading to an initial diagnosis at an advanced incurable stage in the majority of patients. The only potentially curative treatment is radical surgical resection. The effect of current chemotherapeutics or radiotherapy is limited. Novel therapeutic strategies are therefore much needed. One of the hallmarks of PDAC is its abundant desmoplastic (stromal) reaction. The Hedgehog (Hh) signaling pathway is critical for embryologic development of the pancreas. Aberrant Hh signaling promotes pancreatic carcinogenesis, the maintenance of the tumor microenvironment and stromal growth. The canonical Hh-pathway in the tumor stroma has been targeted widely but has not yet lead to hopeful clinical results. Targeting both the tumor and its surrounding stroma through Hh pathway inhibition by also targeting non-canonical pathways as apparent in the tumor cell may therefore be a novel treatment strategy for PDAC. Image: The non-canonical Hedgehog pathway.